Inteligencia emocional en el desempeño laboral de los servidores públicos del grupo de impacto del Cuerpo de Agentes de Control Metropolitano Quito, provincia Pichincha, año 2024. - Pila Armas Katherin Carolina (2025)
This study focuses on understanding how emotional intelligence (EI) affects the job performance of public servants in the impact group of the Metropolitan Control Agents Corps of Quito, Pichincha province, during the year 2024. For this, a mixed methodology was used, using surveys to evaluate emotional intelligence and documentary analysis of the evaluation of the job performance of the servants. The results revealed a significant positive evaluation between emotional intelligence and job performance. The performance evaluations showed an overall average of 90.15, placing it in the “Very Good” category, while the emotional intelligence levels proved to be significantly high in the general analysis, where it was identified that the achievement orientation is a factor of emotional intelligence that predominates most in job performance. The study concluded that the staff has well-developed emotional skills that contribute positively to their professional practice, evidencing outstanding job performance that exceeds the minimum standards required. Based on these findings, it is recommended to implement emotional intelligence training programs within the Annual Training Plan update performance evaluation formats to include emotional competency indicators, and establish internal working groups for the continuous development of emotional skills, taking advantage of the existing organizational structure and optimizing available resources. Keywords: emotional intelligence, job performance, public servants, social skills, effectiveness.